ANALISIS TREN PENCARIAN PADA MESIN PENCARI TENTANG PROVINSI KALIMANTAN SELATAN - Wahyu Ridhoni (Program Studi Teknik Informatika, Politeknik Hasnur, 2015)
The objective of this research is knowing 10 things what most searched by Google’s user about Kalimantan Selatan. Google Trends data for last 5 years from 2010 until 2014 were used as raw material. The first step is started to get primary keywords, generated from explore feature on Google Trends. From this step the secondary specific keyword will be produced. All of the secondary keywords will be analyzed to find the relevancy with the objective of research. Rank calculation was done at the final step. It’s based on index of each Google Trends keyword. The result of this research is the top 10 search keywords about Kalimantan Selatan : (1) Banjarmasin Post, (2) CPNS, (3) Peta, (4)LowonganKerja, (5) BKD, (6) Lagudaerah, (7) Hotel, (8) Bank, (9) LPSE, and (10)Wisata. Keywords: Trend Analysis, Google Trends, Kalimantan Selatan, Search Engine